A study on introducing e-commerce as an innovative strategy in doing business “Pernec Halalsquare”/ Muhammad Faiz Abdul Rahim - Abdul Rahim, Muhammad Faiz (Faculty of Business and Management, 2010)
This case study exploring the components needed in developing a good and effective ecommerce website. Halalsquare is evaluated and determined whether it has the components or not. It is important to have good attribute and quality of website especially in doing online business. In order to justify on what are the organization need to become a good and effective ecommerce website, the observation research has done for 5 months. Through this observation, there are some of issues and elements that related to the online shopping which are customer’s attitudes and behavior, web features and trust. On the other words, this study want to show that besides marketing, the attribute and quality of the website should be give attention. These 3 elements are related to each other. With a good e-commerce website features it helps to gain customer trust. Finding shows that Halalsquare can be concluded as an effective and has the good attribute to become a successful e-commerce website. Hence the answer to overcome lack of sales is strengthening the marketing and promotion activities. Satisfaction is achieved towards the quality of Halasquare portal.